The Indian Diaspora in the UK: Accommodating "Britishness" - Maurice O’Connor (Universitat Autònoma de Barcelona, 2015)
This paper sets out to explore the growth of the Indian diaspora within the UK. First of all, we shall evidence how, despite the humble beginnings of this diasporic community, their strong sense of community and tenacity has helped them gain visibility within British society. From there, we shall look at the complexities of this heterogeneous community and how they have negotiated new spaces within a society that, initially, was hostile to their presence. Despite a prevailing multicultural ethos, we shall then evidence how a system of ‘adjacent cultures’ has been installed within the UK. To further our understanding on this mutual isolation within diversity we shall apply Homi Bhabha’s theories on cultural difference. Then we shall look at a number of biographies and life writings, penned by South Asian authors, so as to elucidate upon this theoretical background.